Strategi Marketing Public Relations Dalam Melakukan Rebranding Lembaga Amil Zakat Persatuan Islam - Rahmani, Tazkia Falah; Hidayat, Dasrun (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Several zakat amil institutions need to implement rebranding strategies with the aim of improving the image and credibility of the institution in the eyes of the public. In 2023, an institution named Pusat Zakat Umat underwent rebranding and changed its name to LAZ PERSIS. This research aims to determine the stages of rebranding in achieving the goal of being recognized again by the general public. The study uses a qualitative method with a descriptive approach. The paradigm used in this research is the constructivist paradigm. The object of this research is the implementation of rebranding carried out by the Zakat Amil Institution PERSIS. The informant selection technique used is non-probability sampling with purposive sampling technique. Data collection methods are carried out through observation, interviews, and documentation. The research results indicate that MPR plays a key role in managing the rebranding transition effectively, building integrated communication, and maintaining public trust.